Semi-Active Damping of Mechanical Vibrating Systems Using Variable Stiffness Actuator - Naji Al-Azzawi, Yarub Omer (Al-Khwarizmi Engineering Journal, 2018)
In this research, a variable stiffness actuator is proposed to enhance the damping of the mechanical vibrating system. The frequency response analysis of the vibrating system is dependant in order to analyze and synthesis this semi-active damping, where the suggested process is using active filter to estimate the present frequency of the vibration system, and this will limit the value of the stiffness of the vibrated system. Two active filter s are needed, low-pass-filter (LPF) to choose the higher stiffness of the actuator at small frequencies as well as more damping and high-pass-filter (HPF) to choose the lower stiffness of the actuator at high frequencies as well as more damping, and so the result will be good damping as a wholre.      These smart systems and others will increase the importance of the mechatronics systems. This job has a case study to explain the semi-active damping system proposed.